Virtual Learning During a Pandemic: Using Technology to Provide and Launch Interactive and Experiential Learning Opportunities for Preservice Teachers - Harshbarger, Dena; Vu, Phu (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2020)
The quick transition to remote learning during the COVID 19 pandemic helped prevent learning from being disrupted at higher educational institutions across the U.S. However, for many instructors and students, this rushed transition to forced online learning without preparation also caused confusion. This paper presents a best practice case study where a college instructor moved her traditional face-to-face, hands-on course to online blended learning (synchronous and asynchronous). Various forms of digital technology were creatively used to teach, model, and engage preservice student teachers in best instructional practices. Lessons learned and a variety of learning activities are shared, and opportunities and challenges are discussed.